Analysis of Quality in Project Quality Management Based on PMBOK® - Didik Suwito Pribadi; Cholid Fauzi; Ardhian Ekawijana (Universitas Pendidikan Indonesia (UPI), 2022)
Quality is a vital part of a successful organization. Quality is important to a process and result. A good process produces a good product, while a good product is produced through a good process. In project management, quality is used to assess project success. Quality is the degree to which the inherent characteristics meet requirements, while project quality is the process of meeting business objectives according to the project charter. The journal entitled 'Analysis of Quality in PMBOK-Based Project Management', discusses the definition, types, and processes of quality management, intending to explain projects and the process of managing them. The benefit is to explain knowledge about quality and its management. The method used is identification, description of the concept of project quality management, analysis of the management planning process, quality control, and conclusions. This research describes the quality management process, including quality control. The main input utilized in the process including Project Charter, PM Plan, Project Documents, EEF, OPA, Approved CR, Deliverables, and Work Performance Data. The Tools and technic utilized in the process include Expert Judgement, Data Gathering, Data Analysis, Decision Making, Data Representation, Test, and Inspection Planning/ audit, Design For X, Problem Solving Quality Improvement Methods, and Meetings. The results obtained from the above process include the main results consisting of QM Plan, Quality Metrics, Quality Reports, Test Documents, CR, QC Measurements, Verified Deliverables, and Work Performance Information.